Chemical Fingerprint and Initial Physicochemical Behavior of Tween 80-Assisted Nanoscale Aqueous Dispersion of Bioactive Java Cardamom Extract: Hydrodynamic Size and Near-Neutral Electrokinetic Profile - Saragih, Horasdia (Department of Agro-industrial Technology, University of Brawijaya, 2026)
AbstractThis study evaluated the chemical profile, hydrodynamic diameter, polydispersity index, electrophoretic mobility, and zeta potential of cardamom extract dispersions. Concentrates were obtained by ethanol extraction of dried cardamom, analyzed using gas chromatography–mass spectrometry, and dispersed at masses of 6, 8, 10, and 12 mg using a liquid–gas flow system. Particle characteristics were determined using a particle size and zeta analyzer. The analysis revealed 14 peaks and 12 identified compounds, with 1,8-cineole, α-terpineol, 3-pentanol (diethyl carbinol), and piperine as the major components. Hydrodynamic diameter increased from 12.0 to 19.2 nm, while polydispersity index increased from 0.084 to 0.492, indicating greater size heterogeneity. Zeta potential ranged from 0.0 to −0.8 mV, indicating weak electrostatic stabilization. Tween 80 likely promoted initial dispersion through steric hindrance and surface hydration rather than strong charge repulsion. These findings do not indicate morphology, encapsulation, temporal stability, or bioavailability. These findings provide a physicochemical basis for developing aqueous cardamom extract dispersions while avoiding overinterpretation of near-neutral zeta potential as evidence of long-term colloidal stability.Keywords: Amomum compactum, cardamom extract, Tween 80, hydrodynamic diameter, zeta potential AbstrakPenelitian ini mengevaluasi profil kimia, diameter hidrodinamik, indeks polidispersitas, mobilitas elektroporetik, dan zeta potential dispersi ekstrak kapulaga. Konsentrat diperoleh melalui ekstraksi etanol kapulaga kering, dianalisis memakai kromatografi gas-spektrometri massa, lalu didispersikan pada massa 6, 8, 10, dan 12 mg melalui sistem alir cair-gas dalam tabung mikro. Karakter diukur menggunakan penganalisis ukuran partikel dan zeta. Analisis kimia menghasilkan 14 puncak dan 12 senyawa teridentifikasi, dengan 1,8-cineole, alpha-terpineol, 3-pentanol atau diethyl carbinol, serta piperine sebagai komponen dominan. Diameter hidrodinamik meningkat dari 12,0 menjadi 19,2 nm. Indeks polidispersitas naik dari 0,084 menjadi 0,492, menandakan distribusi ukuran heterogen. Zeta potential berada dekat netral, yaitu 0,0 sampai -0,8 mV, sehingga stabilisasi elektrostatik diperkirakan lemah. Pendispersian awal mungkin dibantu Tween 80 melalui penghalang sterik dan hidrasi permukaan, bukan tolakan muatan kuat. Temuan ini tidak menyimpulkan morfologi, enkapsulasi, stabilitas temporal, atau bioavailabilitas. Temuan ini memberikan dasar fisikokimia awal untuk mengembangkan sistem dispersi berair dari ekstrak bioaktif kapulaga, sekaligus menghindari interpretasi berlebihan terhadap potensi zeta yang mendekati netral sebagai bukti stabilitas koloid jangka panjang.Kata kunci: Amomum compactum, diameter hidrodinamik, ekstrak kapulaga, Tween 80, zeta potential